Principal Supervision of the Learning Process during Covid-19 Pandemic - Zulfikar Zulfikar; Cut Zahri Harun; Nasir Usman (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study was to document the principal's efforts in overseeing teachers as they implemented in the learning process during the Covid-19 Pandemic. The descriptive method with a qualitative approach was employed in this study. Interviews and observation were used to acquire data. Purposive sampling was used to select the research subjects. The researchers determined the validity of the human instruments themselves. The data analysis process included data reduction, presentation of the data, and conclusion formation. The findings indicated that education supervision in Public Senior High School Bandar Baru District, Pidie Jaya Regency, occurred in different levels, including planning, implementation, and follow-up (evaluation). The principal is responsible for academic oversight, assisted by the vice-principal and senior teachers.